2014
DOI: 10.1080/10705511.2014.919816
|View full text |Cite
|
Sign up to set email alerts
|

Data-Generating Mechanisms Versus Constructively Defined Latent Variables in Multitrait–Multimethod Analysis: A Comment on Castro-Schilo, Widaman, and Grimm (2013)

Abstract: In a recent article, Castro-Schilo, Widaman, and Grimm (2013) compared different approaches for relating multitrait-multimethod (MTMM) data to external variables. Castro-Schilo et al. reported that estimated associations with external variables were in part biased when either the Correlated Traits-Correlated Uniqueness (CT-CU) or Correlated Traits-Correlated (Methods – 1) [CT-C(M – 1)] models were fit to data generated from the Correlated Traits-Correlated Methods (CT-CM) model, whereas the data-generating CT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…However, results of previous studies have shown that the CT-CM modeling approach is associated with various theoretical and empirical problems (e.g., Marsh, 1989; Kenny and Kashy, 1992; Marsh and Grayson, 1994; Steyer, 1995; Eid, 2000; Geiser et al, in press). In addition, the CFA-MTMM model by Grimm et al (2009) is limited to single-indicator measurement designs and does not allow specifying trait-specific method factors.…”
Section: Longitudinal Cfa-mtmm Modelsmentioning
confidence: 99%
“…However, results of previous studies have shown that the CT-CM modeling approach is associated with various theoretical and empirical problems (e.g., Marsh, 1989; Kenny and Kashy, 1992; Marsh and Grayson, 1994; Steyer, 1995; Eid, 2000; Geiser et al, in press). In addition, the CFA-MTMM model by Grimm et al (2009) is limited to single-indicator measurement designs and does not allow specifying trait-specific method factors.…”
Section: Longitudinal Cfa-mtmm Modelsmentioning
confidence: 99%
“…With structurally different methods, each type of structurally different method represents a unique perspective or “fixed effect.” The underlying sampling procedure implies that structurally different methods are “at the same level” with the targets and not nested within the targets (as is the case with interchangeable methods). A meaningful way to compare structurally different methods is thus to contrast them against a reference method, as is done in the CT − C( M − 1) approach (Geiser et al, 2008 , 2014b ). This parallels what is commonly done in regression analysis with fixed categorical predictors, where researchers may use K − 1 dummy code variables to represent the K levels of a fixed factor.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to use the CT-C( M – 1) approach for our extension to mediation analysis, because this approach has been shown to overcome a number of limitations of previous CFA-MTMM approaches. First, in contrast to most other approaches, the CT-C( M – 1) model uses latent variables that have been explicitly and clearly defined as conditional expectations or functions of conditional expectations of observed variables; as a result, all latent variables in the model have a clear meaning and interpretation ( Eid, 2000 ; Eid et al, 2003 ; Geiser et al, 2008 , 2014 ). Second, the CT-C( M – 1) model solves identification problems present in other models ( Eid, 2000 ).…”
Section: A Novel Approach To MI Mediation Analysismentioning
confidence: 99%
“…For example, father’s underestimation of impulsivity relative to mother reports is not necessarily perfectly correlated with father’s underestimation of externalizing problems relative to mother reports. Additional advantages of the CT-C( M – 1) model in relation to other CFA-MTMM models are discussed in Geiser et al (2008) as well as Geiser et al (2014) .…”
Section: A Novel Approach To MI Mediation Analysismentioning
confidence: 99%
See 1 more Smart Citation